(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The aim of this research is to know and define the role and contribution of innovative marketing with its various elements in creating and generating a competitive advantage for companies and business organizations through the provision of new and highly efficient innovative services in the field of communications and Internet services represented by Asia cell in Maysan Governorate as a model for research. The researcher measured a scale of (38) items in order to reveal the relationship, determine the role, the arithmetic averages, the standard deviation, and the values of (one-simple-t test) to answer the questions for the purpose of proving the hypotheses of this study. The study was conducted on (10) random sales points and centers belonging to the company in Missan Governorate The research has proven the existence of a statistically significant and significant correlation between innovative marketing and the competitive advantage, as well as the existence of a statistically significant effect of innovative marketing on the competitive advantage. Adequate equipment, means of communication, promotion and human resources with high skills in dealing with technology